The electoral consequences of immigration : do anti-immigration politicians benefit from the presence of immigrants? - Tvrdoňová, Zuzana (2018)
This paper examines the electoral consequences of immigration based on results of French presidential elections taking place in 2017. Using a hierarchical two-level model as well as an integrated model, the analysis is conducted combining two geographical levels – municipalities and departments/employment areas. The main focus is on the immigration rate in respective areas and its impact on the score of Marine Le Pen in the elections. However, other control variables on the composition of both immigrant and native populations are introduced in our models. The robustness of the results is ensured by accompanying the results of our OLS analysis with results from models with instrumental variable. We challenge findings of DellaPosta (2013) and Rojon (2013) who find that the impact of immigration differs with respect to the geographical level. Specifically, we try to prove that at the level of municipalities the electoral score of Marine Le Pen decreases with raising number of immigrants in the area; whereas at the level of departments, the support for Marine Le Pen is higher with increasing presence of immigrants in the respective area.